Enhancing legal protection for geographical indication products: Strengthening the traditional ikat weaving industry as a local commodity in Gelgel Village, Klungkung District, Klungkung Regency - Asrini, Ni Kadek Putus; Sudiatmaka, Ketut; Sari Adnyani, Ni Ketut Ni; Parwati, Ni Putu Ega (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This study delves into the geographical indication regulations for Klungkung Endek and Songket craft products to ensure legal protection for weaving craftsmen. It is a type of normative legal research employing statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials. Data collection techniques include document study, observation, and interviews, and research analysis involves legal interpretation, which is then described qualitatively. The research findings indicate that Geographical Indication products can enhance regional economic capacity and, as such, must be safeguarded from irresponsible producers' claims practices. The challenges faced by craftsmen are primarily associated with the procedures for registering geographical indication products. Urgent efforts are underway to anticipate issues related to several claims concerning Endek and Songket motifs. The Regional Government of Klungkung Regency, through the Cooperatives and MSMEs Service, is actively providing education to Endek and Songket craftsmen regarding the significance of registering regional products as Geographical Indication Rights with the Director General of Intellectual Property Rights of the Republic of Indonesia. This education encompasses workshops, training sessions, and one-on-one consultations to assist craftsmen throughout the registration process.